Pharmacoepidemiological analysis of antibiotic consumption in 2019 and 2020 – the impact of the COVID-19 pandemic on consumption? - Bojanić, Ljubica; Djermanović, Mirjana; Marković Peković, Vanda; Golić Jelić, Ana (Archives of Pharmacy, 2022)
Antimicrobial resistance (AMR) is one of the most common cause of infections and sepsis that occurs during healthcare and affects hundreds of millions of patients each year, causing almost 20% of all deaths globally, making it one of the biggest public health concerns of today. Most often it occurs due to the irrational antibiotic use. Also, one of the biggest challenges of today is the COVID-19 infection, which due to the complications it causes, many unknown facts and the large number of deaths has led to various therapeutic approaches in treating patients, including the use of antibiotics. The aim of this study is to perform an observational analysis of outpatient antibiotic consumption in 2019 and 2020, before and after the pandemic. Data are obtained from Public Health Institute of the Republic of Srpska and are expressed in defined daily doses/1000 inhabitants/day (DIDs). The data show an increase in total antibiotic consumption by as much as 54% during the observed period (20.2 DIDs in 2019 and 31.1 DIDs in 2020). Given the marked increase in outpatient antibiotic consumption, and that in accordance with the Guidelines for the treatment of patients with COVID-19 infection, antibiotic therapy is not recommended for outpatients, but only for hospitalized patients with moderate clinical picture, a detailed pharmacoepidemiological analysis of outpatient antibiotic consuption is required due to potential irrational use of antibiotics in the treatment of viral COVID-19 infection, and also to take further measures to rationalize consumption and thus reduce antimicrobial resistance.